Homoepitaxial diamond film growth: High purity, high crystalline quality, isotopic enrichment, and single color center formation. Issue 11 (21st October 2015) - Teraji, Tokuyuki; Yamamoto, Takashi; Watanabe, Kenji; Koide, Yasuo; Isoya, Junichi; Onoda, Shinobu; Ohshima, Takeshi; Rogers, Lachlan J.; Jelezko, Fedor; Neumann, Philipp; Wrachtrup, Jörg; Koizumi, Satoshi
Abstract : With optical/electronic devices of the next generation in mind, we provide a guideline for the growth of homoepitaxial diamond films that possess higher crystalline quality, higher chemical purity, and a higher carbon isotopic ratio. A custom‐built microwave plasma‐assisted chemical vapor deposition system was constructed to achieve these requirements. To improve both the purity and crystalline quality of homoepitaxial diamond films, an advanced growth condition was applied: higher oxygen concentration in the growth ambient. Under this growth condition for high‐quality diamond, a thick diamond film of ≥30 μm was deposited reproducibly while maintaining high purity and a flat surface. Then, combining this advanced growth condition for non‐doped diamond with a unique doping technique that provides parts‐per‐billion order doping, single‐color centers of either nitrogen‐vacancy or silicon‐vacancy centers that show excellent properties were formed. The new idea of using these color centers as a probe for detecting tiny amounts of impurities was presented. These advanced growth and characterization techniques are expected to open up new fields of diamond research that require extremely low‐impurity concentration, for use in power devices and quantum information devices. Abstract : Teraji et al. present recent research progress achieved in high‐quality and high‐purity diamond growth. To improve both the purity and crystalline quality of homoepitaxial diamond films, an advanced growth condition was applied: higher oxygen concentration in the growth ambient. With increasing film thickness, morphological patterns (A and B in the images) move to the crystallographic off direction of the substrate. Isotopic enrichment and extremely low concentration doping, which are linked to the study of quantum information devices, are also discussed in this Feature Article.